Assessing the institutional foundations of adaptive water governance in South India - Vallury, Sechindra; Shin, Hoon C.; Janssen, Marco A.; Meinzen-Dick, Ruth S.; Kandikuppa, Sandeep; Rao, R. Kaushalendra; Chaturvedi, Rahul (Resilience Alliance, Inc., 2022)
Institutional structures can fundamentally shape opportunities for adaptive governance of water resources at multiple ecological and societal scales. The properties of adaptive governance have been widely examined in the literature. However, there has been limited focus on how institutions can promote or hinder the emergence of adaptive governance. Elinor Ostrom’s institutional theory stresses the importance of formal and informal norms and rules in effective governance of natural resources. Specifically, Ostrom’s “design principles” (DPs) are considered important because they increase the capacity for adaptive decision making and facilitate the emergence of self-organization at smaller scales. Self-organizing agents can frequently modify rules-in-use, procedures, and technical methods to tackle changing ecological conditions and address significant management issues left by more traditional governments. In this study, we examine institutional arrangements for successful water governance by analyzing (1) the co-occurrence of DPs in irrigation systems, and (2) the combination(s) of DPs leading to social and ecological success. We collaborated with a local non-profit organization to review institutional records and conduct interviews in 50 irrigation communities in Andhra Pradesh and Karnataka in South India. Using qualitative comparative analysis, we found that the effectiveness of design principles is contingent on biophysical properties, such as the size of the watershed being governed, and attributes of the community, such as population size. We also discuss the methodological and data-related challenges involved in collecting primary data for conducting a context-specific institutional analysis. Our study offers a much-needed example of empirical research that investigates the role of operational level rules in adaptive water governance.